Twelve poems attributed to Fland Manistrech from the Book of Leinster - Pődör, Dóra (Trinity College (Dublin, Ireland). Department of Irish and Celtic Studies, 2000)
One of the aims of this thesis is to produce a translated and annotated text of twelve poems attributed to the eleventh-century poet, Flann Manistrech (+1056) from the Book of Leinster (Trinity College Dublin), a manuscript dating from the mid-twelfth century. A diplomatic edition of all of these poems exists, and ten have also been translated before -- nine into English, and one into German. Note that this thesis does not intend to provide a definitive edition of these texts. Another important concern is to give an extensive analysis of the metrical and linguistic features of these poems. Finally, an attempt is made to compare the language of these poems with one another and with Saltair na Rann.
Keywords: Language and Literature. Celtic, Ph.D.; Ph.D. Trinity College Dublin